High Serum AST/ALT Ratio and Low Serum INS*PA Product Are Risk Factors and Can Diagnose Sarcopenia in Middle-Aged and Older Adults - He, Yong; Ding, Fing; Yin, Mengting; Zhang, He; Hou, Lisha; Cui, Tao; Xu, Jinfeng; Yue, Jirong; Zheng, Qin (Frontiers in Endocrinology, 2022)
Background Sarcopenia is an age-related clinical condition and associated with an increased risk of adverse outcomes. However, to date, there is no global standard for the diagnosis of sarcopenia and fewer serum biomarkers have been suggested for the diagnosis of sarcopenia. It is thus important that sarcopenia-related serological diagnostic markers be explored. The present study was based upon the Asian Working Group on Sarcopenia 2019 (AWGS 2019) criteria to assess whether AST/ALT ratio and INS*PA product are a diagnostic marker associated with sarcopenia in various ethnic groups in western China. Methods This cross-sectional study included 4099 adults (1471 men and 2628 women) from the West China Health and Aging Trend (WCHAT) study. The value of serum biomarkers was based on laboratory data. The accompanying metabolic disorders and the associated parameters were evaluated. Logistic regression analysis was used to explore the association between markers and sarcopenia. Receiver operator characteristic curve (ROC) analysis was used to evaluate the diagnostic efficacy of the test in differentiating sarcopenia. Results Binary regression analysis showed that high serum aspartate aminotransferase/alanine aminotransferase (AST/ALT, OR = 2.247) and adrenal cortisol (PTC, OR = 1.511), low serum fasting insulin*prealbumin (INS*PA, OR = 2.970), free triiodothyronine (FT3, OR = 1.313), 25-OH-VitD (VitD, in male, OR = 1.817), and diastolic blood pressure (DBP, in female, OR = 1.250) were independent risk factors for sarcopenia (P < 0.05). AST/ALT and INA*PA were not affected by metabolic factors and had better diagnostic efficacy for sarcopenia. The AUC of the INS*PA was the highest (0.705, 0.706 and 0.701, respectively, P < 0.05), followed by that of AST/ALT (0.680, 0.675 and 0.695, respectively, P < 0.05). The AUC of the AST/ALT/(INS*PA)*10000 used to diagnose sarcopenia was 0.727. Conclusion Among middle-aged and older adults of multiple ethnicities in western China, we found that higher AST/ALT and lower INA*PA level are associated with an increased prevalence of sarcopenia. Since these serum biomarkers are inexpensive and can be obtained easily from biochemical routine, regular follow-up of AST/ALT and INA*PA may be an effective strategy in sarcopenia screening and management.